Awareness and Knowledge of Oral Cancer among University students in Malaysia - Al-Dubai, S.A.R.; Ganasegeran, K.; Alabsi, A.M.; Alshagga, M.A.; Ali, R.S. (2012)
Objectives: This study aimed to assess the level of knowledge of oral cancer and its associated factors among university students in Malaysia. Methods: A cross sectional study was conducted among 200 university students in Malaysia. A self administered questionnaire was used to collect data. It included questions on socio-demographic data, awareness and knowledge of oral cancer. Results: Mean age of the respondents was 21.5+/-2.5 and the age ranged from 18 to 27 years. The majority of the respondents were aware of oral cancer (92.0) and recognized the followings as signs and symptoms of oral cancer: ulcer and oral bleeding (71.0), followed by swelling (61.5). A satisfactory knowledge was observed on the following risk factors; smoking (95.5), poor oral hygiene (90.5), family history (90.0), alcohol (84.5) and poor fitting dentures (83.0). However, unsatisfactory knowledge was observed about hot/spicy food (46.5), obesity (36.0), old age (31.5), dietary factor (29.0) and smokeless tobacco (25.5). Knowledge of oral cancer was associated significantly with age (p<0.01), year of study (p<0.01) and course of study (p<0.01). Conclusion: Instead of satisfactory awareness and knowledge of oral cancer and its clinical presentations, inadequate knowledge was observed about its risk factors. There is a need to introduce oral cancer education among university students.